Low PD-1 expression and no prognostic impact in early-stage Mycosis Fungoides: 61 patients retrospective cohort analysis - Gustavo Moreira Amorim1; 2; 3; Danielle Carvalho Quintella1; João Paulo Niemeyer Corbellini1; Luiz Claudio Ferreira4; Marcia Ramos-; 2; Tullia Cuzzi1; 2; 4 (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2019)
Background: Mycosis fungoides (MF) is an indolent behavior cutaneous T-cell lymphoma. Most patients present a slowly progressive course, over many years. However, some patients evolve early towards advanced stages of the disease, despite adequate treatment, having therefore, a worse prognosis. Increasing knowledge of risk factors that contribute to a better prognostic evaluation is considered of interest. Aims: Evaluate positivity and prognostic importance of PD-1 marker in early-stage MF. Methods: Retrospective cohort study with early-stage MF patients. Cases were defi ned by Pimpinelli criteria. PD-1 positivity was tested in complementary immunohistochemistry over the fi rst skin biopsies done in our hospital. Disease progression, death and MF-related death was investigated 5 years after the date of the diagnostic defi nition according to the proposed criteria. The hazard ratio was calculated as association measurement. Adopted signifi cance criterion was 5%.